EPD Congress 2012 : held during the TMS 2012 annual meeting & exhibition, Orlando, Florida, USA, March 11-15, 2012 - Zhang, Lifeng; Pomykala, Joseph A.; Ciftja, Arjan (EPD Congress,, 2012)
Proceedings symposia sponsored by the Extraction & Processing Division (EPD) of The Minerals, Metals & Materials Society (TMS)Held during the TMS 2012 Annual Meeting & Exhibition Orlando, Florida, USA, March 11-15,2012.